2012
DOI: 10.1021/np2006742
|View full text |Cite
|
Sign up to set email alerts
|

Asperolides A–C, Tetranorlabdane Diterpenoids from the Marine Alga-Derived Endophytic Fungus Aspergillus wentii EN-48

Abstract: Bioassay-guided fractionation of the culture extract of Aspergillus wentii EN-48, an endophytic fungus isolated from an unidentified marine brown algal species of the genus Sargassum, led to the isolation of three new tetranorlabdane diterpenoids, asperolides A-C (1-3), and five related derivatives (4-8). The structures of these compounds were established on the basis of spectroscopic interpretation, and compound 1 was confirmed by X-ray crystallographic analysis. The absolute configuration of 1 was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 25 publications
3
94
0
1
Order By: Relevance
“…have been found in many medicinal plants, including Taxus cuspidate (Zhao et al, 2009), Cephalotaxus mannii (Xue et al, 2012), Melia azedarach . Many antimicrobial compounds had been isolated and characterized from these endophytic fungi, such as diterpenoids (Sun et al, 2012), alkaloids (Zhan et al, 2007;Ding et al, 2012). Cephalosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been found in many medicinal plants, including Taxus cuspidate (Zhao et al, 2009), Cephalotaxus mannii (Xue et al, 2012), Melia azedarach . Many antimicrobial compounds had been isolated and characterized from these endophytic fungi, such as diterpenoids (Sun et al, 2012), alkaloids (Zhan et al, 2007;Ding et al, 2012). Cephalosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…5) (Slack et al 2009;Turner 1971;Turner and Aldridge 1983;Scheweikert 2003, Cole et al 2003), while section Cremei species can produce asperolides, anthraquinonederived bianthrons, leuconic acid, citraconic anhydrides and wentilactones uniquely (Fig. 5) (Verchère et al 1969;Turner 1971;Assante et al 1979;Dorner et al 1980;Selva et al 1980;Turner and Aldridge 1983;Scheweikert 2003, Cole et al 2003;Sun et al 2012). Asperglaucide from Aspergillus restrictus and Aspergillus penicillioides (Itabashi et al 2006) has a clear resemblance to asperphenamate found in Aspergillus flavipes in subgenus Circumdati section Flavipedes (Clark et al 1977).…”
Section: Unique Extrolites In Subgenus Fumigatimentioning
confidence: 99%
“…The reported production of several other mycotoxins by A. wentii was mostly due to species misidentification or is doubtful (Frisvad et al 2005;Frisvad and Larsen 2015). Additional exometabolites were detected in A. wentii and related species by numerous studies (Reid 1975;Qureshi et al 1976;Dorner et al 1980;Selva et al 1980;Hamasaki and Kimura 1983;Frisvad and Samson 1991;Busi et al 2009;Siddhardha 2010;Zhang et al 2012;Xu et al 2015), some of them exhibited various significant biological activities.…”
Section: Introductionmentioning
confidence: 99%